Effects of stabilization training on trunk muscularity and physical performances in youth soccer players - Hoshikawa, Y.; Iida, T.; Muramatsu, M.; Ii, N.; Nakajima, Y.; Chumank, K.; Kanehisa, H. (The Journal of Strength and Conditioning Research, 2013)
The purpose of the present study was to examine the effects of stabilization training on trunk muscularity and physical performances in youth male soccer players aged 12-13 yrs (n = 28). The subjects allocated to training (TG, n = 16) performed a stabilization exercise program consisting of 5 exercises (elbow-toe, elbow-heel, side bridge, modified 1-legged squat, and bent-knee push-up) 4 times per week and a training program specific to soccer 6 times per week, whereas the others (control, n = 12) conducted the soccer training only for 6 months. Before and after the intervention, the cross-sectional areas (CSAs) of 5 muscles (rectus abdominus, oblique, psoas major, quadratus lumborum, and erector spinae) were determined using magnetic resonance imaging. Furthermore, peak torques during hip extension and flexion at 1.05 rad/second, heights of squat and countermovement jumps, and time taken to sprint 15 m were also measured. After 6 months, both groups significantly increased the CSAs of the 5 muscle groups (TG: 4.4-13.4%, control: 5.5-10.9%) and improved sprint time (TG: -1.4%, control: -1.6%), without significant effect of group, but only TG significantly increased the heights of squat (5.0%) and countermovement (6.8%) jumps. In addition, a greater increase in hip extension torque was found in TG (40.8%) than in control (17.4%). The current results indicate that, at least in early adolescent soccer players, adding stabilization exercise to soccer training cannot increase the trunk muscularity, but it will improve hip extensor strength and vertical jump performance.